157 BIASED COMPLEMENTARITY-DETERMINING REGION 3 REPERTOIRES IN SPLEEN MATURE B-LINEAGE CELL POPULATIONS REFLECT PROGRAMMED SELECTION. (1st January 2006) - Tanner, J. M.; Schelonka, R. L.; Zhuang, Y.; Zemlin, M.; Schroeder, H. W.
Abstract : Introduction: The immune repertoire must be diverse to recognize an array of potential antigens, while limiting specificities that react against self. B-lineage cells must survive selection in the bone marrow and then émigrés compete for a niche in secondary lymphoid organs. Survivors incorporate into cellular subsets and localize to well-defined histological sites where they have functionally distinct roles. Objective: To gain insight into the mechanisms of peripheral lymphoid B lineage selection and the role of the immunoglobulin receptor in that process, we sought to establish the pattern of CDR-H3 repertoire development in splenic B-cell populations. Methods: We sorted spleen B-cell fractions from four BALB/cj mice into follicular zone (FZ), marginal zone (MZ), and the first (T1) and second (T2) transitional zone cell populations. VH 7183-D-J-Cμ sequences were deconstructed and analyzed for VH, DH, and JH segment usage, CDR-H3 length, average hydrophobicity, amino acid distribution, and reading frame usage. We compared the CDR-H3 from these B-cell subsets to each other and to CDR-H3 from immature and mature B cells from bone marrow (BM). Results: We sequenced 111 FZ, 110 MZ, 102 T1, and 97 T2 open, in-frame sequences. Splenic B cells used more VH 7183.18, VH 7183.12, V H 7183.13, VH 7183.10, and VH 7183.1 than either immature or mature B cells from BM. MZ B cells used DFL gene segments twice as frequently as T1 and FZ B cells or immature B cells from BM. Conversely, FZ B cells were enriched for use of DSP gene segments. Compared to BM, all four spleen B cell subsets used JH 2 and JH 4 more frequently. On average, MZ and T2 CDR-H3 intervals were one codon shorter than FZ CDR-H3 and a half-codon shorter than T1. T2 and MZ cells were also enriched for highly charged CDR-H3. Conclusions: The composition of the T2 and MZ CDR-H3 repertoires is similar, supporting the view that these populations are highly related. The MZ and FZ repertoires differ in gene utilization, length, and charge, supporting the view that cells in these subsets have been selected based on the specificity of their receptors. The CDR-H3 compositions of all splenic B-cell subpopulations examined differ from those observed in both mature and immature B cells from BM, indicating that antigen receptor-influenced selection has occurred between the exit of cells from the BM and both entry into and exit from the spleen.